PELAKSANAAN PASAL 13 UNDANG-UNDANG NOMOR 18 TAHUN 2012 TENTANG PANGAN TERHADAP PENGENDALIAN HARGA BAHAN POKOK DALAM NEGERI (STUDI DI KANTOR KETAHANAN PANGAN KABUPATEN BLITAR) - Merlinda Yohana Dangung (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2017)
Merlinda Yohana Dangung, Lutfi Effendi, SH.,MH., Dr.Shinta Hadiyantina, SH.,MH Fakultas Hukum Brawijaya Malang Email: Elianamerlinda.yohana@yahoo.com Â  ABSTRAK Ketahanan Pangan di Kabupaten Blitar mengalami kenaikan harga bahan pokok pada hari-hari tertentu, seperti hari raya idhul fitri, idhul adha, hari natal dan pergantian tahun baru. Biasanya kenaikan bahan pokok mencapai 30% dari harga asli. Pelaksanaan aktivitas dan usaha-usaha yang dilakukan oleh Kantor Ketahanan Pangan merupakan kebijakan dari Pemerintah untuk penerapan Pasal 13 Undang-Undang Nomer 18 Tahun 2012 Tentang Pangan. Upaya Pemerintah dalam menangani isu kenaikan harga dibedakan menjadi dua faktor yaitu faktor internal merupakan upaya yang dilakukan dengan menambahkan sumber daya manusia dan adanya kerjasama antara APBD dengan KKP dalam melakukan pengawasan terhadap pengendalian harga bahan pokok, sedangkan faktor selanjutnya yaitu faktor eksternal yang merupakan upaya yang dilakukan adalah mengadakan sosialisasi antara dinas terkait dengan petani dan pedagang agar petani dan pedagang sadar akan bagaimana mendapatkan untung yang tidak merugikan masyarakat. Kata Kunci : PP No. 18/2012 Tentang Pangan, Dalam Negeri. ABSTRACT Food Security in Blitar has increased the price of food on certain days, such as holidays Idhul Fitr, Idhul Adha, Christmas and the new year. Usually the increase in staple up to 30% off the original price. Implementation of the activities and efforts undertaken by the Food Security Office is the policy of the Government to implement Article 13 of Law Number 18 Year 2012 on Food. The Government's efforts in addressing the issue of price rise can be divided into two factors namely internal factor is the effort made by adding human resources and the cooperation between the budget by the CTF in controlling the price controls of basic commodities, while further contributing factor is external factor is the effort made is the socialization between the relevant agencies with farmers and traders to farmers and traders are aware of how to obtain a profit that does not harm society. Food Security in Blitar has increased the price of food on certain days, such as holidays Idhul Fitr, Idhul Adha, Christmas and the new year. Usually the increase in staple up to 30% off the original price. Implementation of the activities and efforts undertaken by the Food Security Office is the policy of the Government to implement Article 13 of Law Number 18 Year 2012 on Food. The Government's efforts in addressing the issue of price rise can be divided into two factors namely internal factor is the effort made by adding human resources and the cooperation between the budget by the CTF in controlling the price controls of basic commodities, while further contributing factor is external factor is the effort made is the socialization between the relevant agencies with farmers and traders to farmers and traders are aware of how to obtain a profit that does not harm society. Keywords: PP 18/2012 About Food, Home Affairs.